PERANCANGAN SISTEM INFORMASI KEPENDUDUKAN UNTUK MENINGKATKAN KUALITAS LAYANAN KEPENDUDUKAN DI DESA GELAM, KAB SIDOARJO - Wahyuni, Hana Catur; Astuti, Mudji (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
Quality of service is an important element to realize people's satisfaction. It is also a driving force for the community to meet its administrative completeness as a citizen. Therefore, this community service activity aims to improve the quality of service through the design of population information system. This activity was held in February to June 2018 in RW 5 Ddesa Gelam region, Kec Candi, Sidoarjo regency. The method of conducting the activity is done through observation, interview, data collection, verification, information system design and graphic flow graph document. The results of community service activities are evidenced through the availability of easy-to-use residence information system and the availability of graphic flow of documents, identity cards, KK, death certificate, marriage certificate, business certificate, domicile letter and birth certificate